Public health impact of achieving 80% colorectal cancer screening rates in the United States by 2018 - Meester, R.; Doubeni, C.; Zauber, A.; Goede, S.; Levin, T.; Corley, D.; Jemal, A.; Lansdorp-Vogelaar, Iris (John Wiley & Sons, Inc., 2015)
BACKGROUND: The National Colorectal Cancer Roundtable, a national coalition of public, private, and voluntary organizations, has recently announced an initiative to increase colorectal cancer (CRC) screening rates in the United States to 80% by 2018. The authors evaluated the potential public health benefits of achieving this goal. METHODS: The authors simulated the 1980 through 2030 United States population of individuals aged 50 to 100 years using microsimulation modeling. Test-specific historical screening rates were based on National Health Interview Survey data for 1987 through 2013. The effects of increasing screening rates from approximately 58% in 2013 to 80% in 2018 were compared to a scenario in which the screening rate remained approximately constant. The outcomes were cancer incidence and mortality rates and numbers of CRC cases and deaths during short-term follow-up (2013-2020) and extended follow-up (2013-2030). RESULTS: Increasing CRC screening rates to 80% by 2018 would reduce CRC incidence rates by 17% and mortality rates by 19% during short-term follow-up and by 22% and 33%, respectively, during extended follow-up. These reductions would amount to a total of 277,000 averted new cancers and 203,000 averted CRC deaths from 2013 through 2030. CONCLUSIONS: Achieving the goal of increasing the uptake of CRC screening in the United States to 80% by 2018 may have a considerable public health impact by averting approximately 280,000 new cancer cases and 200,000 cancer deaths within <20 years.